2010
DOI: 10.4028/www.scientific.net/kem.431-432.265
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Brittle-Ductile Transition in Electroplated Diamond Wire Saw Machining Single Crystal Silicon

Abstract: Based on reciprocating electroplated diamond wire saw (REDWS) slicing experiments, a study on REDWS machining brittle-ductile transition of single crystal silicon was introduced. The machined surfaces and chips were observed by using Scanning Electron Microscope (SEM), and some experimental evidences of the change of material removal mode had been obtained. The experimental results indicate there is a close relationship between material removal mode and the ratio r value of ingot feed speed and wire speed, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The theoretical average cut depths of grits calculated in Table 1 are less than the practical grits average cut depths, due to assuming that all grits taking part in the cutting in theoretical calculation. According to foregoing analysis, the calculation results of No.6, 8, 10, 11 and 12 in Table 1 show there may be ductile regime material removal, which is basically in accordance with the experimental results in references [1].…”
Section: Relationship Between Average Grit Cut Depth and Wire Sawing ...supporting
confidence: 86%
See 1 more Smart Citation
“…The theoretical average cut depths of grits calculated in Table 1 are less than the practical grits average cut depths, due to assuming that all grits taking part in the cutting in theoretical calculation. According to foregoing analysis, the calculation results of No.6, 8, 10, 11 and 12 in Table 1 show there may be ductile regime material removal, which is basically in accordance with the experimental results in references [1].…”
Section: Relationship Between Average Grit Cut Depth and Wire Sawing ...supporting
confidence: 86%
“…Material Removal Model of Grit Cut. In the process of FADWS slicing single crystal silicon, the material removal and chip formation are main in a brittle regime, through brittle cracks intervening and propagating [1]. And the machining process of single diamond grit which is on the wire surface is similar to the single point diamond turning, and the diamond grit has a negative rake, so the diamond grit was assumed as a cone [2].The material removal model of single grit is shown in Fig.…”
Section: Theoretical Analysis Of Grit Cut Depth In Fadws Slicing Sing...mentioning
confidence: 99%
“…The cost of such a cutting takes a con siderable part of the total cost of the plate production. Because of this the investigations of methods to cut with a steel wire, which should combine a high productivity and surface quality attained in ductile removal of the material are the topical task [129][130][131][132][133][134][135]. Up to now, according to the literature, the methods of wire cutting brittle materials, which fully realized ductile mode of cutting, are not developed yet.…”
Section: Ductile Removal Of a Materials In Cutting Brittle Materials Wmentioning
confidence: 99%
“…Up to now, according to the literature, the methods of wire cutting brittle materials, which fully realized ductile mode of cutting, are not developed yet. However, it is indicated that the mechanism of silicon removing in wire cutting may be totally brittle, partially brittle, and near ductile [129][130][131]134]. A totally ductile mode of removing silicon with a diamond wire is described in a theoretical model only [130].…”
Section: Ductile Removal Of a Materials In Cutting Brittle Materials Wmentioning
confidence: 99%
“…The results indicated that a higher surface roughness was observed at the lowest wire speed, whereas the surface roughness varied at different crystal orientations with the same wire speed. Gao and Ge [25] studied the material removal mode on monocrystalline silicon. Their findings showed that the feed rate over the wire speed ratio has a solid relationship with the material removal mode.…”
Section: Introductionmentioning
confidence: 99%